Customer satisfaction on the usage of Singlish in the service industry. - Chew, Min. (2013)
This project aims to examine the impact of the usage of Singlish, which is colloquial English spoken in Singapore. It is an amalgamation of many dialects and languages like English, Teochew, Hokkien, and Malay and it is understood by all Singaporeans.